2004
DOI: 10.1158/1055-9965.epi-03-0076
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Prostate Cancer Risk in the National Health and Nutrition Examination Survey Epidemiological Follow-up Study Cohort

Abstract: Ecological studies implicate a "Western" diet in prostate cancer development, but whether dietary patterns measured in individuals are associated with risk has not been studied previously. We examined this issue using prospective data from the nationally representative United States Health Examination Epidemiological Follow-up Study. Among 3,779 men followed from 1982-84 to 1992, 136 incident cases were identified. Using principal component analysis on responses to a 105-item dietary questionnaire, the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
81
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 35 publications
8
81
1
3
Order By: Relevance
“…21 While different patterns emerge in different study groups and therefore results are not directly comparable, our results are more robust and generally consistent with those from this prospective study. In the present study, we also conducted a comparable analysis to explore individual nutrient values and prostate cancer risk adjusted for the same confounders as the dietary patterns (Table VI).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…21 While different patterns emerge in different study groups and therefore results are not directly comparable, our results are more robust and generally consistent with those from this prospective study. In the present study, we also conducted a comparable analysis to explore individual nutrient values and prostate cancer risk adjusted for the same confounders as the dietary patterns (Table VI).…”
Section: Discussionsupporting
confidence: 83%
“…20 One study to date has assessed dietary patterns in relation to prostate cancer risk, among 136 cases in a cohort of 3,779 men, where frequency of food item consumption was collected prospectively. 21 Higher intake of a ''Southern'' dietary pattern (cornbread, grits, sweet potatoes, etc.) was marginally associated with decreased prostate cancer risk.…”
mentioning
confidence: 99%
“…It is suggested that fat intake, residence in high solar radiation and sun exposure are associated with an increased risk of BCC (van Dam et al, 1999) while monounsaturated fat consumption is associated with a lower risk (van Dam et al, 2000). In a prospective study, high meat and fat intake increased SCC particularly in patients with a family history, (Ibiebele et al, 2007) which was in line with our findings only in men.…”
Section: 1669 Correlation Of Cancer Incidence With Probable Risk Facsupporting
confidence: 91%
“…Many risk factors such as aging, race, family history, gonadal steroids and Insulin-like growth factor I (IGF-I), processed red meat, dairy products and fat (as provoking factors) (Koo et al, 1997;Ngo et al, 2003;Tseng et al, 2004;Schottenfeld and Fraumeni, 2006;Grant, 2010) and cereals, nuts, oilseeds, fish, (Hebert et al, 1998) vitamin E (Schottenfeld and Fraumeni, 2006) soy products (Hebert et al, 1998) and cholesterol (Hu et al, 2012) (as protective factors) have been identified for prostate cancer; in our study dairy products and meat correlated positively and bread and fat negatively with prostate cancer. In a prospective study, prostate cancer was not associated with the vegetablefruit or red meat-starch pattern, but higher intake of the Southern pattern characterized by cornbread, grits, sweet potatoes, okra, beans, and rice showed a significant reduced risk (Tseng et al, 2004). On the other hand, in districts with low education level, prostate cancer was less common, which is in line with other studies (Steenland et al, 2004;Spadea et al, 2009) and might be due to more PSA tests, early detection or more access to healthcare services.…”
Section: 1669 Correlation Of Cancer Incidence With Probable Risk Facmentioning
confidence: 99%
“…9 In our study, the identified dietary patterns were not associated with prostate cancer. Three previous studies [37][38][39] reported rather conflicting results. Therefore, previous studies on prostate cancer did not appear to be related with dietary patterns.…”
Section: Discussionmentioning
confidence: 95%